Mating mediates morphophysiological changes in the spermathecae of Coptotermes gestroi queens - da Silva, Iago Bueno [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Wiley, 2023)
Insect spermathecae play a crucial role in sperm storage and maintenance prior to egg fertilization. Within eusocial insects, this structure is well studied in the Hymenoptera, whose queens copulate during a short period early in life and store sperm for up to decades. Within Isoptera, sperm storage and maintenance inside the spermatheca are poorly understood, especially due to the presence of a sperm-providing king. Here, we compared the morphometric and morphophysiological features of the spermathecae of virgin and mated queens of the invasive termite Coptotermes gestroi (Wasmann) (Isoptera: Rhinotermitidae). The spermatheca comprises a finger-shaped reservoir divided into two regions and a duct limited by a narrow transition. The superficial spermatheca area, as well as the luminal area, increase significantly after insemination, even among queens whose reproductive activity was reduced, suggesting that sperm storage continues during such conditions. The secretion of proteins and polysaccharides into the spermathecal lumen was a remarkable feature for both virgin and 4-year-old queens, although the concentration of the secreted content increased in the latter group. It suggests that spermatheca activation occurs before pairing, but its secretory activity intensifies to nourish and provide energy for the stored spermatozoa. Ultrastructure of the spermathecal epithelium showed a bicellular unit, composed of a secretory cell and associated canal cells. Secretory vesicles of various electron densities were observed next to the receiving canal of the secretory cells in both virgin and 2-year-old queens. Nevertheless, strongly electron-dense vesicles were only recorded for mated queens, which were associated with the increasing synthesis of proteins. The occurrence of rough endoplasmic reticulum and richness of mitochondria reinforces the protein synthesis and transport of contents towards the spermathecal lumen. In conclusion, the spermatheca of C. gestroi undergoes morphometric and physiological changes after mating, and further analysis may provide insights into the chemical nature of the spermathecal secretion prior to and after this event.
Keywords: Blattaria; Coptotermes gestroi; eusocial insect; histochemistry; Isoptera; pest species; reproductive system; Rhinotermitidae; sperm storage; spermatheca; termite; ultrastructure